THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI) AND PRE-EKLAMPSIA IN RSIA AMANAT MAKASSAR CITY - Bunayya Hartadi, Andi Yusnita Latifa; M. Said, Masita Fujiko; Khalid, Nur Fadhillah; Hamsah, M.; Royani, Ida (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The success of maternal health programs is often evaluated using the Maternal Mortality Rate (MMR), which measures deaths during pregnancy, childbirth, and the puerperium due to pregnancy-related causes. In 2020, hypertension in pregnancy was a leading cause of maternal deaths, with 1,110 cases reported. Pre-eclampsia, characterized by hypertension (blood pressure ≥140/90 mmHg) and proteinuria after 20 weeks of gestation, is a significant concern. Overweight and obesity are high-risk factors associated with increased pregnancy complications, including pre-eclampsia. This study aimed to analyze the relationship between Body Mass Index (BMI) and pre-eclampsia at Amanat Hospital in Makassar City. Using an observational analytic design with a cross-sectional approach, 284 pregnant women were assessed. The prevalence of pre-eclampsia was found to be 9.9%, with 28 women diagnosed. Bivariate analysis using the Chi-Square test revealed a significant association between BMI and pre-eclampsia (p = 0.001), while no significant association was found between Upper Arm Circumference (LILA) and pre-eclampsia (p = 0.348). The study concludes that BMI is significantly associated with pre-eclampsia, whereas LILA does not show a significant relationship.